Evolution of structure functions in momentum space - Tuomas Lappi; Heikki Mäntysaari; Hannu Paukkunen; Mirja Tevio (European Physical Journal C: Particles and Fields)
Abstract We formulate the momentum-space Dokshitzer–Gribov–Lipatov-Altarelli–Parisi (DGLAP) evolution equations for structure functions measurable in deeply inelastic scattering. We construct a six-dimensional basis of structure functions that allows for a full three flavor structure and thereby provides a way to calculate perturbative predictions for physical cross sections directly without unobservable parton distribution functions (PDFs) and without the associated scheme dependence. We derive the DGLAP equations to first non-zero order in strong coupling $$α _s$$ α s , but the approach can be pursued to arbitrary order in perturbation theory. We also numerically check our equations against the conventional PDF formulation.